INVESTIGATING COSMETIC ADVERTISEMENT’S FIGURE OF SPEECH ON COMMERCIAL TELEVISION IN INDONESIA - Bambang Nur Alamsyah Lubis; Friska Triana (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
Advertising is one of the essential types of mass communication expected to persuade people to buy a product or service. In advertising, the use of language must be persuasive because it affects to influence consumers to buy these goods. Using figurative expressions in advertising is one way to attract the attention of consumers. This qualitative study aims to determine the types of figurative expressions and functions used in advertised cosmetic advertisements on Indonesian television. The data of this research are cosmetic advertisements that are broadcast on Indonesian television in 2022 which express English figurative expressions in advertising slogans. Based on the 10 data identified, the researchers find that all of them share figurative expressions of various kinds. The expression find in this research is hyperbole. It has been found that from 10 advertisements. After analyzing the data obtained in Cosmetic Advertisements on Television, there are 5 figurative languages in Cosmetic Advertisements. There are: Personification, Repetition, Hyperbole, Metaphor and Simile.